Peran Lembaga Keuangan Syariah pada Pengelolaan Keuangan Usaha Mikro Kecil dan Menengah (Studi pada UMKM yang Ada di Kelurahan Pintu Air) - Mulyani, Hendarti Tri Setyo; Iswanto, Yuni (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2024)
The growth of MSMEs is very important and should be noticed by the government. With small capital, these relatively small businesses can significantly contribute to the growth of the country's economy. However, on the other hand, capital often becomes a constraint for MSME entrepreneurs. In addition to operational needs, capital is also crucial for the development of their businesses. One institution responsible for finance based on Islamic teachings, as outlined in the Qur'an and Sunnah, is the Islamic Financial Institution (LKS). LKS aims not only to be profit-oriented but also to incorporate elements of Islam and humanity in its vision and mission. Strengthening the role of MSMEs in economic growth, especially in the Water Gate sub-district of Pangkalpinang City, Bangka Belitung Islands Province, is expected to have a positive impact on the local economy. However, the role of Islamic Financial Institutions in supporting MSMEs in this sub-district is still minimal. This is due to the lack of socialization of products and financial management practices from Islamic Financial Institutions, which results in a low level of interest from MSME actors to use Islamic financial products or implement Islamic financial management in their businesses. Interviews and observations conducted with several MSME actors in the Water Gate sub-district of Pangkalpinang City indicate that while financing has been received by some MSMEs, only a few MSME actors in this area have benefited from KUR financing from Islamic Financial Institutions due to limited knowledge and information about these institutions. Furthermore, regarding education and counseling, 4 out of 5 MSME actors interviewed reported that they have not received direct education from Islamic Financial Institutions about the implementation of Islamic finance or Islamic financial management for their businesses.